Acute impact of blood flow restriction during resistance exercise – review - Gawel, Dawid; Jarosz, Jakub; Matykiewicz, Patryk; Kaszuba, Magdalena; Trybulski, Robert (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Athletes, as well as recreationally trained individuals are increasingly looking for innovative techniques and methods of resistance training to provide an additional stimulus to break through plateaus, prevent monotony and achieve various training goals. Partial or total blood flow restriction (BFR) to the working muscles during resistance exercise has been used as a complementary training modality, aiming to further increase muscle mass and improve strength. BFR is usually used during low-load resistance exercise and has been shown to be effective in enhancing long-term hypertrophic and strength responses in both clinical and athletic populations. However, recently some attention has been focused on the acute effects of BFR on strength and power performance during highload resistance exercise. Aim of Study. This article provides an overview of available scientific literature and describes how BFR affects the 1-repetition maximum (1RM), the number of repetitions performed, time under tension and kinematic variables such as power output and bar velocity. Material and Methods. Available scientific literature. Results. As a result, BFR could be an important tool in eliciting greater maximal load, power output and strength-endurance performance during resistance exercise. Conclusions. BFR as a training tool can be used as an additional factor to help athletes and coaches in programming varied resistance training protocols.
Keywords: occlusion; cuff; ischemia; bar velocity; 1RM test; repetition